Minimum Tillage and in situ Mulch Increasing the Population and Biomass of Earthworms Under Mung Bean Cultivation on Ultisol Soil - Aini, Septi Nurul; Yusnaini, Sri; Tunsiyah, Tunsiyah; Niswati, Ainin (JOURNAL OF TROPICAL SOILS, 2019)
Earthworms are important soil biota that can be used as  an indicator of soil fertility. Soil tillage systems and application of organic mulch will affect the activity of earthworms. This research was aimed to study the effect of tillage systems and the application of in situ mulch, and their interactions on the population and the biomass of earthworms. The study was conducted from April to July 2017 at the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. The study was arranged in a Randomized Block Design (RBD) in a factorial treatment with two factors.  The first factor was the tillage system  which consisted of the minimum tillage and the intensive tillage. The second factor was the application of in situ mulch, which consisted of the application of 0 Mg ha-1 or without mulch and the application of 5 Mg ha-1  in situ mulch.The data obtained were tested for homogeneity of variance with the Bartlett Test and its additivity with the Tukey Test. Data were further analyzed for the analysis of variance and for the LSD’s Test at the level of 5%. The relationship between soil temperature, soil moisture content, soil organic-C and soil pH with population and biomass earthworm was tested by correlation test. The results showed that the earthworm population and the earthworm biomass at 80 DAP in the minimum tillage  was higher than that of the intensive tillage. The earthworm population for all detected planting stages (before tillage, 40 DAP and 80 DAP) with the of application of 5 Mg ha-1 in situ mulch was higher than that of the application of no mulch.  There is no interaction between the tillage system and the application of in situ mulch at 0 DAP, 40 DAP, and 80 DAP.  The genus of earthworms found in all treatment plots was genus Pheretima under the family of Megascolecidae.